CD99 is a potential diagnostic and immunological biomarker in pan-cancer - Juntao Jiang; Zuoxiao Han; Haizhu Zhang; Hao Chen (Discover Oncology)
Abstract Background As a cell adhesion factor, cluster of differentiation 99 (CD99) mainly plays a role in regulating cell differentiation. In cancer research, CD99 primarily focuses on sarcoma. Recent studies have revealed that CD99 plays a critical role in the initiation and progression of several cancers. However, a comprehensive pan-cancer analysis of CD99 has not been performed. Methods In this study, we utilized advanced bioinformatics techniques to conduct an in-depth investigation of CD99 expression across diverse tumors, its prognostic and diagnostic implications, the predominant modes of genetic alteration, correlations with immune cell infiltration and immune checkpoints, enrichment analyses of related gene expression, and mechanisms of drug resistance. Results Our findings revealed that CD99 was significantly upregulated in numerous common cancers and was associated with both diagnostic and prognostic outcomes. Notably, genetic alterations of CD99 predominantly manifest as deletions in sarcoma. Furthermore, CD99 exhibited strong correlations with nearly all infiltrating immune cells and their corresponding checkpoints. Enrichment analyses further emphasized the potential role of CD99 in epithelial-mesenchymal transition (EMT) pathways and leukocyte migration. Additionally, our investigations into drug resistance indicated that CD99 expression was primarily linked to resistance against antitumor agents such as 5-fluorouracil and belinostat. Conclusions Through this comprehensive pan-cancer analysis, we elucidated novel roles for CD99 in various cancer types, providing important insights for clinical treatment strategies and drug development.